Ectopic Defense Gene Expression Is Associated with Growth Defects in Medicago truncatula Lignin Pathway Mutants . Issue 1 (9th July 2019) - Man Ha, Chan; Fine, Dennis; Bhatia, Anil; Rao, Xiaolan; Martin, Madhavi Z.; Engle, Nancy L.; Wherritt, Daniel J.; Tschaplinski, Timothy J.; Sumner, Lloyd W.; Dixon, Richard A.
Abstract : Growth defects arising from lignin modification are associated with the extent, but not the nature, of ectopic expression of defense pathways. Abstract: Lignin provides essential mechanical support for plant cell walls but decreases the digestibility of forage crops and increases the recalcitrance of biofuel crops. Attempts to modify lignin content and/or composition by genetic modification often result in negative growth effects. Although several studies have attempted to address the basis for such effects in individual transgenic lines, no common mechanism linking lignin modification with perturbations in plant growth and development has yet been identified. To address whether a common mechanism exists, we have analyzed transposon insertion mutants resulting in independent loss of function of five enzymes of the monolignol pathway, as well as one double mutant, in the model legume Medicago truncatula . These plants exhibit growth phenotypes from essentially wild type to severely retarded. Extensive phenotypic, transcriptomic, and metabolomics analyses, including structural characterization of differentially expressed compounds, revealed diverse phenotypic consequences of lignin pathway perturbation that were perceived early in plant development but were not predicted by lignin content or composition alone. Notable phenotypes among the mutants with severe growth impairment were increased trichome numbers, accumulation of a variety of triterpene saponins, and extensive but differential ectopic expression of defense response genes. No currently proposed model explains the observed phenotypes across all lines. We propose that reallocation of resources into defense pathways is linked to the severity of the final growth phenotype in monolignol pathway mutants of M. truncatula, although it remains unclear whether this is a cause or an effect of the growth impairment.